Influencing factor analysis of water invasion in condensate gas reservoir with bottom water based on fuzzy comprehensive evaluation and orthogonal experiment. Issue 6 (2nd November 2019) - Yan, Wende; Qi, Zhilin; Yuan, Yingzhong; Huang, Xiaoliang; Li, Jiqiang
ABSTRACT: Condensate oil and water invasion coexist in the condensate gas reservoir with bottom water. Because of influences of condensate oil pollution and water invasion, gas recovery obviously decreases. There are many factors influencing water invasion in a condensate gas reservoir with bottom water, including static petrophysical properties and dynamic operational conditions. Various factors play different roles in the process of water invasion, and the comprehensive effects of them on water invasion are difficult to be determined because these factors interfere with each other. With gas reservoir engineering method and numerical simulation technology, the factors including acuifer size, height of water avoidance, permeability, effective gas pay thickness, condensate oil saturation and gas well production rate on water invasion are researched. Water breakthrough time, stable production period and gas recovery are calculated for different cases under different parameter combinations through fuzzy comprehensive evaluation and orthogonal experiment design. Then sensitivities of these factors are analyzed and main factors influencing water invasion are selected and sequenced. The research supply theoretical basis for preventing and controlling water invasion thus improves development effect of condensate gas reservoir with bottom water.